Conceptual model of mobile augmented reality for cultural heritage site towards enjoyable informal learning aspect - Chandini Pendit, Ulka; Zaibon, Syamsul Bahrin; Abu Bakar, Juliana Aida (Penerbit UTM Press, 2015)
Conceptual model of mobile augmented reality (AR) for cultural heritage site based on enjoyable informal learning aspect is proposed to help technical or content developers to develop mobile AR application specifically for cultural heritage site that include enjoyable learning aspect.The conceptual model provides appropriate content, navigation and user interface design, interactivity, features, hardware, and process for providing informal learning in enjoyable way at cultural heritage site using mobile AR. The conceptual model consists of three structures, six components, and twenty nine elements.The usage of conceptual model is flexible which can be implemented according to developer’s needs and preferences.